Long-Run Purchasing Power Parity (Doktrin Paritas Daya Beli) dengan the Error Correction Model - Utami, Nunung Nurastuti (Akutansi Bisnis & Manajemen ( ABM ), 2004)
This research investigated the short and long run validity and reability of purchasinb power parity (PPP). Error Correction Model (RCM( is employed to examine pooled data of Indonesia-US exchange rate. Wholesale price indices and consumer price indices are gathered from IFS. The findings suggest that either short or long run Purchasing Power Parity do not hold.